EVALUATION OF THE SEDIMENT MANAGEMENT PLAN IN A FORESTED STEEP CATCHMENT RESERVOIR - Ida Bagus Gede Indrayana; Kurniawan Putra Santoso; Fransisca Natania Karina Rediasti (Universitas Udayana, 2025)
Gerokgak Reservoir in northern Bali plays a key role in supporting irrigation for Subak Gede Gerokgak. However, ongoing sedimentation threatens its storage capacity and long-term performance. This study evaluates the sedimentation risk management plan by Balai Wilayah Sungai (BWS), focusing on the effectiveness of the current dredging schedule and storage allocation. Using the Universal Soil Loss Equation (USLE) with land use, topographic, and rainfall data, the annual sediment yield was estimated at 29,277.85 m³, with a Sediment Delivery Ratio of 18.6 percent. Comparison with historical data showed only a 3 percent margin of error. Without additional dredging, dead storage is projected to be filled within 8 years, far before the 20-year target in the current plan. To meet that target, 0.59 million m³ of storage is needed, requiring 0.299 million m³ of extra dredging. These findings underscore the need to integrate sediment yield analysis into planning for more adaptive and effective reservoir management